A Bibliometric Study on Corporate Transparency and Disclosures. Issue 2 (June 2023) - Bhimavarapu, Venkata Mrudula; Rastogi, Shailesh; Mulay, Preeti
Corporate transparency is a critical requirement for effective governance. Through a thorough financial regulation, it has the potential to influence investors' investment decisions in a company. The global financial crisis, in the past, has prompted a high level of openness worldwide since it frequently implies the quality of information disclosure. To make investment decisions, investors rely on the information provided by the firms. Hence it is crucial to have an encyclopaedic understanding of corporate disclosures. This research employs bibliometric analysis from a multi-industry approach to systematically synthesize and improve corporate transparency and disclosures. For 23 years, 410 journal articles were collected from the Scopus database between 1998 and 2021. This article highlights the publication trend and identifies the most influential work, authors, countries and journals. Finally, the Author, Journal and keyword co-occurrence have expressed the article's research themes through thematic progression. Lastly, the article highlights the gaps in the literature and makes recommendations for further research.